Penerapan Strategi Pembelajaran Aktif untuk Meningkatkan Partisipasi Siswa di MA Al-Ittihadiyah PKL Masyhur Medan - Ihsan, Ikhlasul (Journal of Sustainable Education, 2025)
Low levels of student participation during the learning process have become a major challenge at MA Al Ittihadiyah PKL Masyhur Medan. The lack of student engagement not only affects their comprehension of the subject matter but also hinders the overall achievement of learning objectives. This study aims to improve student participation through the implementation of various active learning strategies designed to involve students more directly in classroom activities. The research employed a Classroom Action Research (CAR) method, conducted in multiple cycles. Data were collected through observation, interviews, questionnaires, and documentation of classroom activities. The active learning strategies applied included group discussions, role-playing, and the think-pair-share method. The results revealed a significant increase in student participation after the implementation of these strategies. Students became more active in expressing opinions, asking questions, working collaboratively in groups, and showed greater enthusiasm and interest in learning. It can be concluded that a systematic and well-planned application of active learning strategies effectively enhances student participation and engagement in the classroom.